PENGARUH MEDIA AUDIOVISUAL DALAM KEMAMPUAN SISWA MENULIS PUISI - Yuliani Dwi Prutanti; Yunus Abidin; Fully Rakhmayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
At this time poetry writing activities are less attractive to elementary school students even to the level of higher education students. This is due to their difficulty in determining themes, words and of course they are difficult to realize their fantasies in real life. Because writing this poem is writing that contains the results of one’s thought and feelings. Writing poetry can be easier and more fun if you use the right and enjoyable media. In this study, the aim was to see the magnitude of the influence of audiovisual media to improve students’ ability to write poetry. In this study using the literature review methode. This research shows that audiovisual media is very influential in improving students’ ability to write poetry. In this study, using the results of several studies that have been verified, the results show an increase as evidenced by the increasing number of percentages compared to before using audiovisual media.